Association between urinary propylene oxide metabolite and the risk of dyslexia. (1st January 2022) - Liu, Qi; Wan, Yanjian; Zhu, Bing; Xie, Xinyan; Zhu, Kaiheng; Jiang, Qi; Feng, Yanan; Xiao, Pei; Xiang, Zhen; Wu, Xiaoqian; Zhang, Jiajia; Meng, Heng; et al.
Abstract: Although it is a probable human carcinogen, propylene oxide is widely applied in industry and daily life. However, data on neurodevelopmental effects of propylene oxide exposure among children are extremely limited. We aimed to determine the urinary concentrations of propylene oxide metabolite among school-aged children and evaluate the potential association of propylene oxide exposure with risk of dyslexia. A total of 355 dyslexic children and 390 controls were recruited from three cities (Jining, Wuhan, and Hangzhou) in China, between 2017 and 2020. Urinary N-acetyl-S-(2-hydroxypropyl)-L-cysteine (i.e., 2-hydroxypropyl mercapturic acid; 2-HPMA) was measured as the biomarker of propylene oxide exposure. The detection frequency of 2-HPMA was 100%. After adjusting for potential confounders, the odds ratio (OR) for dyslexia per 2-fold increase in urinary 2-HPMA was 1.19 [95% confidence interval (95% CI): 1.01, 1.40, P  = 0.042]. Compared with the lowest quartile of urinary 2-HPMA concentrations, children with the highest quartile of 2-HPMA had a 1.63-fold (95% CI: 1.03, 2.56, P  = 0.036) significantly increased risk of dyslexia, with a dose-response relationship ( P -trend = 0.047). This study provides epidemiological data on the potential association between propylene oxide exposure and the risk of dyslexia in children. Further studies are warranted to confirm the findings and reveal the underlying biological mechanisms. Graphical abstract: Image 1 Highlights: School-aged children in China were extensively exposed to propylene oxide. Urinary 2-HPMA levels differed significantly by sex, age, and smoking exposure. Urinary propylene oxide metabolite was positively associated with risk of dyslexia.